2011
DOI: 10.1371/journal.pone.0024339
|View full text |Cite
|
Sign up to set email alerts
|

Meibum Lipid Composition in Asians with Dry Eye Disease

Abstract: BackgroundPrevious lipidomic analyses of the human meibum had largely focused on individuals from non-Asian populations, despite the higher prevalence of dysfunctional tear syndrome (DTS) observed across Asia. Information pertaining to the alterations in lipid profiles in relation to DTS onset and progression is also lacking and warrants comprehensive experimental analysis.Methodologies/Principal FindingsWe examined the meibum lipidome of 27 DTS patients and 10 control subjects for a total of 256 lipid species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(227 citation statements)
references
References 45 publications
17
201
6
Order By: Relevance
“…Lipid profiles of meibum are highly variable with 2-fold variation in CE abundance between individuals 11,21 . This high variability of lipid profiles has also been shown in the CE abundance in human tears 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid profiles of meibum are highly variable with 2-fold variation in CE abundance between individuals 11,21 . This high variability of lipid profiles has also been shown in the CE abundance in human tears 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive overview of the molecular lipid composition of human tears has recently been realized through application of contemporary mass-spectrometric analytical tools [10][11][12] . The advancements in instrumentation and extraction techniques have overcome challenges of small sample size and low overall lipid concentration, allowing the analysis of un-pooled samples, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We adhered to the tenets of the Declaration of Helsinki for all human research conducted in this study. The detailed clinical procedures have been reported elsewhere ( 10 ).…”
Section: Study Groupmentioning
confidence: 99%
“…7,9,10 Specifically, some components of lens care solutions significantly alter dynamic interfacial properties and rheological behavior of human tear lipid films. [11][12][13] Clinical results suggest that both Asian and non-Asian groups exhibited increased corneal staining in response to biguanidepreserved solutions, although Asian subjects demonstrated greater sensitivity to the solutions than did non-Asian subjects. 4 However, the severity of ocular signs does not always correlate with overall lens wear comfort in Asian subjects, and thus may not be an impediment to overall satisfaction.…”
Section: Adverse Events During Contact Lens Wearmentioning
confidence: 99%
“…Studies conducted in China and Japan reported a much higher prevalence of dry eye syndrome (DES) than in previous reports, 12,13 suggesting that Asians may be more predisposed to DES than non-Asians. 11 In addition, Hispanic and Asian women in the United States were more likely to report severe dry eye symptoms when compared with white women. 77 Another research group came to a similar conclusion for Asian subjects.…”
Section: Symptomatology: Dryness and Discomfort With Contact Lens Wearmentioning
confidence: 99%